Peningkatan Kapasitas Sekretaris Desa Dalam Pelayanan Publik: Studi Deskriptif Kualitatif di Desa Libunio, Kecamatan Soa, Kabupaten Ngada, Nusa Tenggara Timur - Maria Vinsensia Beku (CV. Ulil Albab Corp, 2023)
This study uses a qualitative descriptive approach to explain the capacity building of the Village Secretary in public services in Libunio Village, Soa District, Ngada District. Data was collected through in-depth interviews and participatory observation in several villages. The results of the study show that the Village Secretary faces challenges in service quality caused by limited knowledge, skills and resources. Capacity building efforts have been carried out through training, participation in professional networks and collaboration with related parties. This research provides recommendations for expanding training, accessing adequate resources, and stronger collaboration with stakeholders. The results of this study can be used to improve the quality of public services at the village level.